2013
DOI: 10.1002/ldr.2204
|View full text |Cite
|
Sign up to set email alerts
|

Soil Structural Stability and Water Retention Characteristics Under Different Land uses of Degraded Lower Himalayas of North‐West India

Abstract: The lower Himalayan regions of north-west India experienced a severe land-use change in the recent past. A study was thus conducted to assess the effect of grassland, forest, agricultural and eroded land uses on soil aggregation, bulk density, pore size distribution and water retention and transmission characteristics. The soil samples were analysed for aggregate stability by shaking under water and water drop stability by using single simulated raindrop technique. The water-stable aggregates (WSA) >2 mm were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 35 publications
2
38
0
1
Order By: Relevance
“…Root biomass and SOM were observed as supporting material for the formation of aggregates (Figure 3). In many studies, it has been revealed that GL and AAO have the annual mean maximum root biomass, and an estimated annual root biomass was noted in grassland at 1360 kg and 6803 kg hac −1 year −1 [59][60][61]. The findings of this study showed that the surface soil at 0-20 cm in GL and AAO contained the highest amounts of root biomass and SOM (Figure 3) while that in CAO contained the lowest root biomass and Clw contained a greater amount than Clm.…”
Section: Effects Of Root Biomass In the Different Land-use Systemsmentioning
confidence: 99%
“…Root biomass and SOM were observed as supporting material for the formation of aggregates (Figure 3). In many studies, it has been revealed that GL and AAO have the annual mean maximum root biomass, and an estimated annual root biomass was noted in grassland at 1360 kg and 6803 kg hac −1 year −1 [59][60][61]. The findings of this study showed that the surface soil at 0-20 cm in GL and AAO contained the highest amounts of root biomass and SOM (Figure 3) while that in CAO contained the lowest root biomass and Clw contained a greater amount than Clm.…”
Section: Effects Of Root Biomass In the Different Land-use Systemsmentioning
confidence: 99%
“…Soil genesis and soil degradation comprise a worldwide issue that is researched by different strategies (Laudicina et al, 2015;Parras-Alcántara et al, 2015;Saha and Kukal, 2015;Srinivasarao et al, 2014). There is a need for research that will contribute to sustainable soil management (Bisantino et al, 2015;Mekonnen et al, 2015;Ndah et al, 2015;Wildemeersch et al, 2015) and that will assist policy makers in finding a way to apply the findings and achieve the sustainability .…”
Section: Introductionmentioning
confidence: 99%
“…The results provided an insight into the significance for land use and farming water management in this area. Saha and Kukal (2015) found that there is a relationship between soil structural stability and land use. The results indicated the degradation of soil physical attributes due to the conversion of natural ecosystems to farming system and increased erosion hazards.…”
Section: Landformmentioning
confidence: 99%